Drake's Great Armada - Bigges, Walter, -1586 (Salt Lake City, UT : Project Gutenberg, 2006)
"Drake's Great Armada" by Captain Walter Biggs is a historical account detailing Sir Francis Drake's remarkable West Indian voyage that began in 1585. Written in the early 20th century, the book explores the significant military endeavors against Spain, a backdrop of rising tensions between England and Spain, leading up to the famous events of Drake's plundering of Spanish territories and shipping. The narrative chronicles the audacity and adventurous spirit of the time, punctuated by Drake$1 (Bs strategies and the considerable challenges his fleet faced. In this detailed narrative, Biggs recounts the events of the expedition, from the meticulous preparations of a fleet of 25 ships and 2,300 men to the conquest of key locations like Santiago, Santo Domingo, and Cartagena. As Drake and his men engage in fierce battles, suffer from deadly fevers, and grapple with the challenges of colonial warfare, the story emphasizes Drake's leadership and the camaraderie among the captains. The narrative serves both as a thrilling account of naval warfare and an insightful look into the implications of the actions taken during this expedition, which contributed to the shift in power dynamics between England and Spain in the late 16th century. Despite the high stakes and numerous casualties faced, including the loss of many men to disease, the voyage culminated in significant treasure and resources for England, marking a decisive period in British maritime history. (This is an automatically generated summary.)s
Release date is 2006-04-06
Produced by Dagny; John Bickers; David Widger
Keywords: Explorers -- Great Britain -- Biography; Drake, Francis, approximately 1540-1596 -- Travel -- West Indies; West Indies Expedition, 1585-1586; Explorers -- America -- Biography